Perbandingan Penanda Inflamasi dan Elastisitas Vaskular antara Mahasiswa Kedokteran Prehipertensi dan Normotensi di Jakarta - Wibowo, Naufal Rafi Kusuma; Bustamam, Nurfitri; Bahar, Meiskha; Purwaningastuti, Diana Agustini (Jurnal Kedokteran Meditek, 2025)
Introduction: An unhealthy lifestyle among medical students may contribute to inflammation, reduced vascular elasticity, and increased blood pressure. However, cardiovascular risk in these young adults remains less explored compared to hypertensive patients. Purpose: This study compares inflammatory markers and vascular elasticity in prehypertensive and normotensive medical students. Methods: A case-control study utilizing simple random sampling was conducted in the medical student population, included 54 prehypertensive or normotensive subjects with no history of hematological disorders, autoimmune diseases, cancer, diabetes mellitus, or cardiovascular medication use. Vascular elasticity, blood pressure, and inflammatory markers were assessed using an accelerated photoplethysmograph, a digital sphygmomanometer, and a hematology analyzer. Results: A total of 25 subjects (46.3 %) had suboptimal vascular elasticity, 30 (55.6%) had a high neutrophil-to-lymphocyte ratio (NLR), and 40 (74.1%) exhibited a low-risk platelet-to-lymphocyte ratio (PLR). The Chi-square test revealed a significant difference in NLR between prehypertensive and normotensive students (p = 0.000; OR = 7.0; CI = 2.3–20.7), while no significant difference was observed in PLR (p = 0.525). Vascular elasticity also differed significantly between groups (p = 0.000; OR = 5.2; CI = 2.0-13.2). Conclusion: Prehypertensive subjects had higher NLR, and those with suboptimal vascular elasticity had higher prehypertension risk. These findings highlight the need for cardiovascular risk assessment in young adults.